Las actas de mediación sobre derechos indisponibles y su ejecución. - Aldaz Muñoz, Washington Vinicio (2024)
The Constitution of the Republic recognizes alternative means for resolving conflicts, in matters that by their nature are transmissible, which ensures a quick and timely solution, while helping to decongest the administration of justice. Mediation is an alternative method of conflict resolution that is based on negotiation between the parties involved. In Ecuador, mediation is regulated by the Arbitration and Mediation Law. Mediation can be used to resolve any type of conflict, regarding available rights. However, the enforcement of mediation agreements on unavailable rights can be problematic, as these agreements may go against the law or the rights of third parties. It should be noted that mediation is carried out before a neutral third party, who is responsible for carrying out the steps to reach an agreement. This neutral third party is not always knowledgeable or versed in legal science and law, in such a way There is no assurance that the agreement is on transmissible matters nor that this agreement is subsequently enforceable. Keywords: Mediation, unavailable rights, mediation record.